Estrategia(s) de desarrollo regional bajo el nuevo escenario global-local: revisión crítica sobre su(s) potencialidad(es) y límites - Víctor Ramiro Fernández (EURE, 2001)
This work analyzes the approaches that support the strategic positions ofregions into the new glocalizator scenery. After presenting an empiricalcountercurrent that ended, during the 90, weakening the argumentsabout the horizontality and harmonic expansion of the territorialcomplexes of flexible accumulation at global level, the work examinedthe approaches that, assuming this scenery, hold the relevance of thedevelopment of a solid regional-local orgware and qualified networks ofcooperation, in order to give continuity to the centrality of regions. Theweakness of the these new development were evaluated, highlighting: a)the re-invocation to empirical cases with historical specificity, that makedifficult their transference; and b) the scarce presence of national spacesand the state